2018
DOI: 10.1186/s12941-018-0295-4
|View full text |Cite
|
Sign up to set email alerts
|

Adherent/invasive Escherichia coli (AIEC) isolates from asymptomatic people: new E. coli ST131 O25:H4/H30-Rx virotypes

Abstract: BackgroundThe widespread Escherichia coli clone ST131 implicated in multidrug-resistant infections has been recently reported, the majority belonging to O25:H4 serotype and classified into five main virotypes in accordance with the virulence genes carried.MethodsPathogenicity Islands I and II (PAI-I and PAI-II) were determined using conventional PCR protocols from a set of four E. coli CTXR ST131 O25:H4/H30-Rx strains collected from healthy donors’ stool. The virulence genes patterns were also analyzed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“… 47 Barrios-Villa et al reported four ST131 E. coli strains isolated from healthy humans with a high adherence/invasive phenotype. 48 …”
Section: Discussionmentioning
confidence: 99%
“… 47 Barrios-Villa et al reported four ST131 E. coli strains isolated from healthy humans with a high adherence/invasive phenotype. 48 …”
Section: Discussionmentioning
confidence: 99%
“…18,32 Virotypes of all 101 ST131 isolates were determined as previously described. 18,33 Virotype C was most common, represented by 38/101 (37.6%) of…”
Section: Virotypesmentioning
confidence: 99%
“…18, 31 Virotypes of all 101 ST131 isolates were determined as previously described. 18, 32 Virotype C was most common, represented by 38/101 (37.6%) of ST131 isolates and predominantly associated with bla CTX-M-27 (28/38 isolates) across clades A (n=3), C1-M27 (n=22), C1-nM27 (n=4), and one isolate belonged to an unclassified clade. All bla CTX-M-27 -positive isolates belonged to virotype C, with the exception of one isolate for which a virotype could not be assigned.…”
Section: Resultsmentioning
confidence: 99%